Effects of speed on EMG and kinematic parameters in freestyle - Rouard, A. H.; Quezel, G.; Billat, R. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of this study was to investigate the evolution of kinematic and electromyographic parameters with increasing speed in freestyle. Fifty subjects (30 males, 20 females) with average age of over 18.1 years were tested. The subjects performed 2 x 25 m at 4 different speeds: 75%, 85%, 95% and 100% of their best performance over 100 m. Side-underwater video views were obtained and simultaneously EMGs of 6.muscles of the upper limb were recorded with a telemetric system. The MGs, normalised to the highest values found throughout the test, were related to hip displacement and the total time of the stroke uslng ·principal component analysis. Results indicated that swimmers increased their speed by decreasing the total time of the stroke and by sustaining their hip displacements. A linear relationship between speed and muscular activity was not observed. The six muscles studied had their higher activities for the.iowest and highest speed and their lower recruitments for the intermediate paces. The greater activities of the legs, associated with a higher position of the body on the water, could explain the lower muscular activities of the upper limb for the intermediate speeds.